Analisis Kemampuan Pemecahan Masalah Matematis : Dampak Model Pembelajaran Superitem Berbantuan Scaffholding - Raya, Ahmad Kausar; Soleh, Sofyan M; Wulandari, Heny (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to determine the effect of the use of the super-scaled model of scaffolding on students' mathematical problem solving abilities. The sampling technique used was cluster random sampling with 3 classes namely experimental class 1 (the class was treated with scaffolding assisted superememe learning model), experimental class 2 (superitem learning only) and control class (the conventional treatment class). Hypothesis testing used is anava 1 cell path is not the same. The results of the study found that there were differences in students' mathematical problem solving abilities by using learning models of scaffolding assisted supermarkets. Furthermore, the mathematical problem solving ability of students with the super-intensive learning model assisted by scaffholding is the same as the mathematical problem-solving ability of students using superemit learning models. The mathematical problem solving ability of students with superficial learning models assisted by scaffholding is better than the students' mathematical problem-solving abilities using conventional learning models. Furthermore, the mathematical problem solving ability of students with superemit learning models is the same as the mathematical problem solving ability of students using conventional learning models.